Control of blood pressure in Scotland: the rule of halves. Issue 6730 (14th April 1990) - Smith, W C; Lee, A J; Crombie, I K; Tunstall-Pedoe, H
Abstract : OBJECTIVE--Audit of detection, treatment, and control of hypertension in adults in Scotland. DESIGN--Cross sectional survey with random population sampling. SETTING--General practice centres in 22 Scottish districts. SUBJECTS--5123 Men and 5236 women aged 40-59 in the Scottish heart health study, randomly selected from 22 districts throughout Scotland, of whom 1262 men and 1061 women had hypertension (defined as receiving antihypertensive treatment or with blood pressure above defined cut off points). MAIN OUTCOME MEASURE--Hypertension (assessed by standardised recording, questionnaire on diagnosis, and antihypertensive drug treatment) according to criteria of the World Health Organisation (receiving antihypertensive treatment or blood pressure greater than or equal to 160/95 mm Hg, or both) and to modified criteria of the British Hypertension Society. RESULTS--In half the men with blood pressure greater than or equal to 160/95 mm Hg hypertension was undetected (670/1262, 53%), in half of those in whom it had been detected it was untreated (250/592, 42%), and in half of those receiving treatment it was not controlled (172/342, 50%). In women the numbers were: 486/1061, 46%; 188/575, 33%; and 155/387, 40% respectively. Assessment of blood pressure according to the British Hypertension Society's recommendations showed an improvement, but in only a quarter of men and 42% of women was hypertension detected and treated satisfactorily (142/561, 215/514 respectively). IMPLICATIONS--The detection and control of hypertension in Scotland is unsatisfactory, affecting management of this and other conditions, such as high blood cholesterol concentration, whose measurement is opportunistic and selective and depends on recognition of other risk factors.